La dottrina costituzionale di Sieyès - Marco, Goldoni (Strumenti per la didattica e la ricerca, 2009)
The reception and popularity of the work of Emmanuel Joseph Sieyès has gone through different and erratic phases. Nonetheless, in recent years there has been a remarkable revival of interest in the Abbé's thought. This book is intended to exploit this Sieyès-renaissance, proposing a reconstruction of the constitutional doctrine of the abbot in the light of the latest interpretative acquisitions. The guiding thread of the analysis is the acknowledgement that, underlying the main political-constitutional proposals of Sieyès, we can glimpse a profoundly rationalist philosophical substructure. After presenting the nucleus of this philosophical approach, the book proceeds to shed light on the coherence linking the main constitutional structures upon which the abbot was working in the course of the early years of the Revolution. It focuses in particular on the concepts that contributed to make up the basic grammar of modern and liberal constitutionalism: representation, citizenship, constituent power, rights of man, the division of the powers and the control of constitutionality. The idea is that, by pursuing this approach, it is possible to arrive at an overall picture of the constitutional doctrine of the abbot that reflects both its systematic quality and its originality.